2020
DOI: 10.1002/ccd.29003
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and clinical outcomes of bleeding complications and acute limb ischemia in STEMI and cardiogenic shock

Abstract: Background Bleeding complications and acute limb ischemia (ALI) are devastating vascular complications in patients with ST‐segment elevation myocardial infarction (STEMI). Cardiogenic shock (CS) can further increase this risk due to multiorgan failure. In the contemporary era, percutaneous mechanical circulatory support is commonly used for management of CS. We hypothesized that vascular complications may be an important determinant of clinical outcomes for CS due to STEMI (CS‐STEMI). Objective We evaluated 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 50 publications
2
20
0
Order By: Relevance
“…This is one of the largest studies to holistically review and discuss complications of pLVAD and IABP use in AMI-CS. Prior studies from the HCUP-NIS database have discussed individual complications specifically, but have not investigated the broad categories of clinically relevant complications that are reviewed in the present study [37,40,41]. Our results are consistent with prior work demonstrating that pLVAD has a higher overall complication rate when compared to IABP [6,20,22,23,42].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This is one of the largest studies to holistically review and discuss complications of pLVAD and IABP use in AMI-CS. Prior studies from the HCUP-NIS database have discussed individual complications specifically, but have not investigated the broad categories of clinically relevant complications that are reviewed in the present study [37,40,41]. Our results are consistent with prior work demonstrating that pLVAD has a higher overall complication rate when compared to IABP [6,20,22,23,42].…”
Section: Discussionsupporting
confidence: 88%
“…Lastly, this study showed a temporal increase in complication rates amongst both cohorts, contrary to the expected decrease in complication rates that should occur with increased operator experience over time. Given the administrative nature of the database, it is possible that these trends could be a function of systematic changes in coding over time similar to other literature published on this topic from the HCUP-NIS database [40,41]. Further investigation is needed to determine patient-specific factors that may better delineate optimal candidates for pLVAD versus IABP and adherence to guideline-directed use of these MCS devices.…”
Section: Plos Onementioning
confidence: 91%
“…Similarly, bleeding occurred in 19.4%, 29.9%, and 54.2% of each group, respectively, while limb ischemia occurred in 0.9%, 3.6%, and 7.7%, respectively. All of these complications were associated with increased length of stay and hospitalization costs 22 , 23 . While it stands to reason that more invasive devices would lead to higher complication rates, it must be noted that these observational studies do not account for significant baseline differences between the real-world patients in whom the devices are deployed.…”
Section: Putting Recent Safety Signals Into Contextmentioning
confidence: 99%
“…So, in this relatively small study, lower rates of bleeding observed with radial access did not translate into improved survival. Similarly, others have shown that acute bleeding in CS patients was not associated with higher mortality, once one controlled for the higher baseline risk in patients who bled 3,4 . This suggests that mortality in CS patients is primarily related to factors other than bleeding (such as multiorgan failure, anoxic encephalopathy, progressive heart failure), unless of course, serious bleeding occurs.…”
mentioning
confidence: 91%